Databases of Publications and Observations as a Part of the Crimean Astronomical Virtual Observatory - Shlyapnikov A. (Open Astronomy, 2015)
We describe the main principles of formation of databases (DBs) with information about astronomical objects and their physical characteristics derived from observations obtained at the Crimean Astrophysical Observatory (CrAO) and published in the “Izvestiya of the CrAO” and elsewhere. Emphasis is placed on the DBs missing from the most complete global library of catalogs and data tables, VizieR (supported by the Center of Astronomical Data, Strasbourg). We specially consider the problem of forming a digital archive of observational data obtained at the CrAO as an interactive DB related to database objects and publications. We present examples of all our DBs as elements integrated into the Crimean Astronomical Virtual Observatory. We illustrate the work with the CrAO DBs using tools of the International Virtual Observatory: Aladin, VOPlot, VOSpec, in conjunction with the VizieR and Simbad DBs.